Leg strength and power in Polish striker soccer players - Busko, K.; Górski, M. Nikolaidis, P. T.; Mazur-Rózycka, J.; Lach, P.; Staniak, Z.; Gajewski, J. (Acta of Bioengineering and Biomechanics, 2018)
Purpose: The main goal of the present study was to examine muscle strength and power of dominant and non-dominant leg, knee extensors and flexors, and their correlations with jumping performances in soccer players. A secondary aim was to evaluate muscle sense. Methods: 31 male professional strikers (age 20.9 ± 2.3 years, body mass 75.1 ± 6.6 kg, body height 179.5 ± 4.7 cm) participated in the study. The power output of lower extremities and the height of rise of the body mass centre during vertical jumps were measured using a force plate. The maximum muscle torque of the flexors and extensors of the knee were measured under isometric conditions using a special isometric torquemeter. Force sense was measured in isometric conditions in two tests: (a) fifty percent of the maximal voluntary contraction was set as a value of target force and the participants were instructed to reproduce the target force, (b) the participants attempted to develop a torque reproducing a sine course within the range of 10 to 50% of MVC performed. Results: A direct relationship was observed between the peak muscle torque in knee extensors developed during isokinetic contraction at all velocities and power and height of three types of vertical jumps ( p < 0.05). No correlation was observed between jumping performance and muscle torque under isometric condition. No differences were found in strength and jumping abilities as well as in force sense between dominant and non-dominant legs. Conclusions: This study offered a comprehensive and complete evaluation of leg muscle strength, sense and power, with the use of using force plate and isokinetic dynamometry